CARACTERIZAÇÃO TERMOGRAVIMÉTRICA DA DEGRADAÇÃO DO SOLO LATERITA. - SANTOS JUNIOR, Benedito Amauri; SOUZA, Armando Cirilo; SOUZA, Naelmo; MICHELS, Flávio Santana; VARGAS, Luiz Felipe Plaça (ANAIS DO ENIC, 2023)
-